Mechanistic Analysis of the Influence of Curing Processes on the Microstructural Development and Durability of Concrete in Hot and Semi-Arid Climates: A Synthetic Review - Rupidara, Yohanes; Remigildus Cornelis (Universitas Bojonegoro, 2026)
Hot and semi-arid climates present critical challenges to concrete performance due to rapid water evaporation and the interruption of cement hydration. Curing, as the post-casting phase, functions to maintain adequate temperature and moisture to ensure complete hydration. This paper presents a mechanistic synthesis of six major international studies analyzing the effect of curing on microstructural development and durability of concrete under hot and semi-arid environments. Findings show that curing effectiveness strongly depends on maintaining thermal and moisture stability within the first 3–7 days. Methods such as film curing, moist curing, and thermal–moisture insulation curing (TMIC) effectively reduce water loss by up to 40% and increase compressive strength by 20–35% compared to uncured specimens. Mechanistically, effective curing enhances the formation of dense Calcium Silicate Hydrate (C–S–H) gels, reduces porosity, and improves resistance to chloride ion penetration. The synthesis concludes that adaptive climate-based curing strategies are crucial for ensuring long-term durability of concrete infrastructures, especially in semi-arid regions like East Nusa Tenggara, Indonesia.